Лазеріндукована інтерстиціальна термотерапія солітарних вузлів щитоподібної залози — перший досвід - Шідловський, О. В.; Карел, О. І.; Шідловський, В. О. (Clinical Endocrinology and Endocrine Surgery, 2009)
The preliminary analysis of the results from prescribing the Laser Diathermocoagulation as a method of treatment in 47 patients who had different clinical forms of nodular goiter shows that it is clinically effective and has no adverse postoperative effect.